- #1

Icebreaker

[tex]f(x,y,z,u,v)=xe^y+uz-\cos v=2[/tex]

[tex]g(x,y,z,u,v)=u\cos y+x^2v-yz^2=1[/tex]

I need to find [tex]u_z[/tex]. When I try to do it by implicitly differentiating and solving the equation, I get 2 contradictory answers. If I try the formula, i.e.

[tex]f_z + f_uu_z + f_vv_z = 0[/tex]

[tex]g_z + g_uu_z + g_vv_z = 0[/tex]

I get an answer, but I'm not sure if it's right, since it does not equal to the answer I get when I differentiate implicitly. Any help?

Also I'm not entirely sure if my "formula" is right. Maybe this formula is just implicit differentiation, I haven't looked into it.

[tex]g(x,y,z,u,v)=u\cos y+x^2v-yz^2=1[/tex]

I need to find [tex]u_z[/tex]. When I try to do it by implicitly differentiating and solving the equation, I get 2 contradictory answers. If I try the formula, i.e.

[tex]f_z + f_uu_z + f_vv_z = 0[/tex]

[tex]g_z + g_uu_z + g_vv_z = 0[/tex]

I get an answer, but I'm not sure if it's right, since it does not equal to the answer I get when I differentiate implicitly. Any help?

Also I'm not entirely sure if my "formula" is right. Maybe this formula is just implicit differentiation, I haven't looked into it.

Last edited by a moderator: